Методика экспериментальных исследований линейных импульсных электромеханических преобразователей - Болюх, В.Ф.; Кочерга, А.И.; Олексенко, С.В.; Щукин, И.С. (Електротехніка і електромеханіка, 2017)
Разработана методика экспериментальных исследований, которая состоит в одновременной регистрации электрических и механических силовых и скоростных параметров линейного импульсного электромеханического преобразователя. При работе преобразователя в качестве ударно-силового устройства силовые показатели регистрируются с
использованием пьезодатчика, системы тензодатчиков, датчика пульсации давления и скоростной видеосъемки. При
работе преобразователя в качестве электромеханического ускорителя скоростные показатели регистрируются с
использованием резистивного датчика перемещений. Показано, что электромеханические процессы в преобразователе носят сложный пространственно-временной характер. Результаты экспериментальных исследований удовлетворительно согласуются с расчетными показателями, полученными при помощи математической модели, которая
описывает быстропротекающие электромагнитные, тепловые и механические процессы, возникающие при перемещении якоря относительно индуктора. Розроблено методику експериментальних досліджень, яка полягає у одночасному реєструванні електричних та механічних параметрів лінійного імпульсного електромеханічного перетворювача. При роботі в якості ударно-силового
пристрою силові показники реєструються з використанням пьєзодатчика, системи тензодатчиків, датчика пульсації тиску та швидкісної відео зйомки. При роботі перетворювача в якості електромеханічного прискорювача швидкісні показники реєструються з використанням резистивного датчика переміщень. Показано, що електромеханічні
процеси в перетворювачі носять складний просторово-часовий характер. Результати експериментальних досліджень
задовільно узгоджуються з розрахунковими показниками, які отримані за допомогою математичної моделі, що описує
швидкоплинні електромагнітні, теплові та механічні процеси, що виникають при переміщення якоря відносно індуктора. Purpose. Development of a technique of experimental studies
linear pulse electromechanical converters parameters, which are
used as shock-power devices and electromechanical accelerators,
and comparing the experimental results with the calculated indices obtained using the mathematical model. Methodology.
Method of experimental investigations of linear electromechanical
converter is that the electrical parameters are recorded simultaneously (inductor winding current) and mechanical parameters
characterizing the power and speed indicators of the joke with
actuator. Power indicators are primarily important for shockpower devices, and high velocity - for electromechanical accelerators. Power indices were investigated using piezoelectric
sensors, a system of strain sensors, pressure pulsation sensor and
high-speed videorecording. Velocity indicators were investigated
using a resistive movement sensor which allows to record character of the armature movement with actuating element in each
moment. Results. The technique of experimental research, which
is the simultaneous recording of electrical and mechanical power
and velocity parameters of the linear electromechanical converter
pulse, is developed. In the converter as a shock-power device
power indicators are recorded using a piezoelectric transducer,
strain sensors system, pressure pulsation sensor and high-speed
video. The parameters of the inductor winding current pulse, the
time lag of mechanical processes in relation to the time of occurrence of the inductor winding current, the average speed of the
joke, the magnitude and momentum of electrodynamics forces
acting on the plate strikes are experimentally determined. In the
converter as an electromechanical accelerator velocity performance recorded using resistive displacement sensors. It is shown
that electromechanical converter processes have complex spatialtemporal character. The experimental results are in good agreement with the calculated figures obtained by means of a mathematical model that describes the ultrafast electromagnetic, thermal and mechanical processes that occur when the yoke moves
relative to the inductor. Originality. For the first time offered
during experimental studies of impulse linear electromechanical
converter to both to measure the electrical parameters, namely the
inductor winding current, and mechanical parameters characterizing the power and velocity performance with yoke actuator.
Practical value. The technique of experimental investigations the
parameters of the linear pulse electromechanical converter that
can be used to investigate the shock-power devices and electromechanical accelerators is proposed